Analisis Deiksis Pada Humor Balada Wanyad dan Darkonah (Kajian Pragmatik) - Hermawan, Didi (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
There are two languages in Brebes; Javanese and sundanese Brebes. The study focuses on Humor in Javanese language Brebes dialect. People living in Brebes has a particular humor, such as Balada Wanyad dan Darkonah which is well-known in the regency. There were several investigations regarding the language and the use of pragmatic in it. The aim of this paper is to figure out how the description and analysis of Deixis on humor Balada Wanyad dan Darkonah. The result of the research indicates that the most deixis and deictic appearing is personal deixis, showed as follows; 47 person deixis (31,33 %), 38 Temporal deixis (25, 33 %), 46 social deixis (30, 66 %), 8 spatial deixis (5, 33 %), 11 discourse deixis (7, 33 %).